2021
DOI: 10.3389/fphys.2021.642299
|View full text |Cite
|
Sign up to set email alerts
|

Irritant Inhalation Evokes P Wave Morphological Changes in Spontaneously Hypertensive Rats via Reflex Modulation of the Autonomic Nervous System

Abstract: Irritant inhalation is associated with increased incidence of atrial fibrillation (AF) and stroke. Irritant inhalation acutely regulates cardiac function via autonomic reflexes. Increases in parasympathetic and sympathetic reflexes may increase atrial susceptibility to ectopic activity and the initiation of arrhythmia such as AF. Both age and hypertension are risk factors for AF. We have shown that irritant-evoked pulmonary–cardiac reflexes are remodeled in spontaneously hypertensive (SH) rats to include a sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Recent studies have pointed out that upregulation of the sympathetic nervous system is an important mechanism underlying obesity-related hypertension. [38,39,42,43] Also, leptin released by adipose tissue disturbs the hypothalamic neuronal systems, which can subsequently reduce food consumption, upregulate energy expenditure, and stimulate sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have pointed out that upregulation of the sympathetic nervous system is an important mechanism underlying obesity-related hypertension. [38,39,42,43] Also, leptin released by adipose tissue disturbs the hypothalamic neuronal systems, which can subsequently reduce food consumption, upregulate energy expenditure, and stimulate sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue, once thought to be a simple energy warehouse, is now recognized to interact with systemic inflammatory responses, the sympathetic nervous system, and the renin-angiotensin system, facilitating obesity-related cardiometabolic dysregulation and contributing to the development of hypertension. Recent studies have pointed out that upregulation of the sympathetic nervous system is an important mechanism underlying obesity-related hypertension [38,39,42,43] . Also, leptin released by adipose tissue disturbs the hypothalamic neuronal systems, which can subsequently reduce food consumption, upregulate energy expenditure, and stimulate sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The latter effect was explained as a brief hypertensive phase followed by a hypotensive phase occurring secondary to TRPA1 channel activation associated with stimulation of autonomic sensory neurons [ 213 ]. In SHRs alone, AITC caused abnormal electrocardiogram (ECG) pattern with increased occurrence of negative P and duration of P waves, and also increased PR and RR intervals than in controls [ 214 ].…”
Section: Mechanism Of Cardio- and Neuroprotective Effectmentioning
confidence: 99%
“…However, caution is needed in clinical trials involving heart disease patients. Therefore, the inhalational route might not be a good gateway for AITC treatment for patients with background heart disease and hypertension [ 214 ].…”
Section: Mechanism Of Cardio- and Neuroprotective Effectmentioning
confidence: 99%
“…During sympathetic stimulation, the action potential of the atrial muscle cell is shortened; the slope of phase 0 increases; the refractory period is compressed; the automaticity is elevated; the triggering activity is enhanced, and the P wave voltage, P wave maximum time, and P wave dispersion can be significantly increased [ 12 , 33 ]. Hooper et al [ 34 ] observed a significant and positive increase in P wave duration when rats inhaled allyl isothiocyanate (AITC), an experimental agent exciting the sympathetic nerves. Cheema et al [ 12 ] observed that epinephrine infusion prolonged P wave duration in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%